The Roles and the Influences of Political Parties in the Parliament towards the Formation of Islamic Bank in Indonesia - Dwi Andayani Budisetyowati (Universitas Lampung, 2018)
The Islamic Banking has been growing significantly in Indonesia. However, studies discussed the detail of the roles and the influences of the political parties in the parliament towards the formation and the development of the Islamic Banks had been limited. Due to this condition, this paper aims at discussing the roles and the influences of the political parties in the parliament towards the formation and the development of Islamic Banks in Indonesia. The method used to examine the above issues is by conducting desk research. Data and information collected are from the secondary sources and the empirical studies advanced in the literature. The study argued that the Islamic banking had been given a social and economic contribution to the Indonesian economy. However, support for the formation and development of this bank is still limited. For that reason, it is a must for the Government of Indonesia in general and the Bank of Indonesia in particular to support the development of Islamic bank. Also, the role of the political parties in the parliament was also considered important. Thus, much remain to be done. Keywords: Islamic Banks, Parliament, Regulation, Bank of Indonesia, Formation, Development